Pertumbuhan Bisnis Melalui Metode O2O pada Usaha Mikro, Kecil dan Menengah (UMKM) di Indonesia - Wardhanie, Ayouvi Poerna; Kartikasari, Puspita; Wulandari, Sri Hariani Eko (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2018)
The government's efforts to encourage Micro, Small and Medium Enterprises (MSMEs) to "go online" get great support from the business people of e-commerce.This is because the economic power, especially in Indonesia with 60% lies in MSMEs. In the current mobile internet era, the number of smartphone users who have done online is the main source in the development of MSMEs. One of the strategies adopted by many businesses in Indonesia is the Online to Offline or Offline to Online (O2O) strategy.The O2O business model not only changes consumer mentality and service models but also bring a new challenge to the traditional e-commerce. It can be said that e-commerce is currently looking for new ways to combine online and offline economics, which is an inevitable trend in e-commerce development.Therefore, the O2O business model is the right business model for MSMEs because it has great development prospects. This paper will discuss the introduction of the O2O model and its development strategy to MSMEs, as well as to promote the development of O2O-based e-commerce applications at MSMEs.